Rapamycin Suppresses Mossy Fiber Sprouting But Not Seizure Frequency in a Mouse Model of Temporal Lobe Epilepsy - Buckmaster, Paul S. (Society for Neuroscience, 2011)
Temporal lobe epilepsy is prevalent and can be difficult to treat effectively. Granule cell axon (mossy fiber) sprouting is a common neuropathological finding in patients with mesial temporal lobe epilepsy, but its role in epileptogenesis is unclear and controversial. Focally infused or systemic rapamycin inhibits the mammalian target of rapamycin (mTOR) signaling pathway and suppresses mossy fiber sprouting in rats. We tested whether long-term systemic treatment with rapamycin, beginning 1 d after pilocarpine-induced status epilepticus in mice, would suppress mossy fiber sprouting and affect the development of spontaneous seizures. Mice that had experienced status epilepticus and were treated for 2 months with rapamycin displayed significantly less mossy fiber sprouting (42% of vehicle-treated animals), and the effect was dose dependent. However, behavioral and video/EEG monitoring revealed that rapamycin- and vehicle-treated mice displayed spontaneous seizures at similar frequencies. These findings suggest mossy fiber sprouting is neither pro- nor anti-convulsant; however, there are caveats. Rapamycin treatment also reduced epilepsy-related hypertrophy of the dentate gyrus but did not significantly affect granule cell proliferation, hilar neuron loss, or generation of ectopic granule cells. These findings are consistent with the hypotheses that hilar neuron loss and ectopic granule cells might contribute to temporal lobe epileptogenesis.